2008
DOI: 10.1021/cg0704753
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Guanine Crystals from the Skin of Fish May Be Designed to Enhance Light Reflectance

Abstract: ABSTRACT:The metallic luster from the skin of fish is due to a photonic crystal system composed of multilayer stacks of cytoplasm and crystals. The crystals are described as thin (50-100 nm) plates of guanine, with no reference to their hydration state. We established through X-ray diffraction that their crystal structure is that of anhydrous guanine. We noted that their crystal structurefunction relationship is exceptional compared to other purines with similar molecular stacking of the crystal structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(178 citation statements)
references
References 28 publications
5
173
0
Order By: Relevance
“…5a). (2) As found in scales of fish, in other biological reflectors the planar purine molecules in reflective crystals are also oriented parallel to the broad face of the crystal platelets (Greenstein, 1973;Levy-Lior et al, 2008). Although in the orthogonal case reflected light is polarized slightly more strongly ( Fig.…”
Section: Orientation Of Guanine Moleculesmentioning
confidence: 89%
See 2 more Smart Citations
“…5a). (2) As found in scales of fish, in other biological reflectors the planar purine molecules in reflective crystals are also oriented parallel to the broad face of the crystal platelets (Greenstein, 1973;Levy-Lior et al, 2008). Although in the orthogonal case reflected light is polarized slightly more strongly ( Fig.…”
Section: Orientation Of Guanine Moleculesmentioning
confidence: 89%
“…In fish scales, the planar purine molecules lie essentially parallel to the broad face of the crystals in the x-y-plane (henceforth called the "parallel case"; Fig. 6a, middle sketch), resulting in n x = 1.85, n y = 1.80 and n z = 1.46 (Greenstein, 1973;Levy-Lior et al, 2008). For normal light incidence on the plate (θ i = 0 • ) along the z−axis, reflection is high for light oscillating both along the x−axis and the y−axis since the refractive index differences between crystal and cytoplasm is high for both e-vector orientations (1.85 vs. 1.33 along the x−axis, 1.80 vs. 1.33 along the y−axis).…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33) A shining mechanism of guanine crystals has also been reported. 34,35) This explains why the skin of gnomefishes and other such fish with a metallic color have a large amount of guanine (296.7 mg/100 g for the gnomefish skin, 105.8 mg/100 g for sardine).…”
Section: Amount Of Purines In Fresh Fishmentioning
confidence: 90%
“…8 An anhydrous guanine crystal has parallel stacked guanine molecules. 9 In the previous studies, it was found that biogenic guanine crystals showed a quick response to external magnetic fields where the crystal platelets oriented parallel to the magnetic field and distinctly switched the intensity of light reflection. [10][11][12][13] The present study focused on assessing the dynamic behaviour of guanine by using synthetic guanine crystals.…”
Section: Introductionmentioning
confidence: 99%